Forkhead box M1B is a determinant of rat susceptibility to hepatocarcinogenesis and sustains ERK activity in human HCC. Issue 5 (9th January 2009) - Calvisi, D F; Pinna, F; Ladu, S; Pellegrino, R; Simile, M M; Frau, M; De Miglio, M R; Tomasi, M L; Sanna, V; Muroni, M R; Feo, F; Pascale, R M
Abstract : Background and aim: Previous studies indicate unrestrained cell cycle progression in liver lesions from hepatocarcinogenesis-susceptible Fisher 344 (F344) rats and a block of G1 –S transition in corresponding lesions from resistant Brown Norway (BN) rats. Here, the role of the Forkhead box M1B ( FOXM1 ) gene during hepatocarcinogenesis in both rat models and human hepatocellular carcinoma (HCC) was assessed. Methods and results: Levels of FOXM1 and its targets were determined by immunoprecipitation and real-time PCR analyses in rat and human samples. FOXM1 function was investigated by either FOXM1 silencing or overexpression in human HCC cell lines. Activation of FOXM1 and its targets (Aurora Kinose A, Cdc2, cyclin B1, Nek2) occurred earlier and was most pronounced in liver lesions from F344 than BN rats, leading to the highest number of Cdc2–cyclin B1 complexes (implying the highest G2 –M transition) in F344 rats. In human HCC, the level of FOXM1 progressively increased from surrounding non-tumorous livers to HCC, reaching the highest levels in tumours with poorer prognosis (as defined by patients' length of survival). Furthermore, expression levels of FOXM1 directly correlated with the proliferation index, genomic instability rate and microvessel density, and inversely with apoptosis. FOXM1 upregulation was due to extracellular signal-regulated kinase (ERK) and glioblastoma-associated oncogene 1 (GLI1) combined activity, and its overexpression resulted in increased proliferation and angiogenesis and reduced apoptosis in human HCC cell lines. Conversely, FOXM1 suppression led to decreased ERK activity, reduced proliferation and angiogenesis, and massive apoptosis of human HCC cell lines. Conclusions: FOXM1 upregulation is associated with the acquisition of a susceptible phenotype in rats and influences human HCC development and prognosis.